Salivary vitamin D3 in relation to dental caries among pregnant women in Baghdad city - Abed, Maimonah T; Radhi, Nada J (Journal of Baghdad College of Dentistry, 2022)
Background: Vitamin D deficiency is a problem for pregnant women, and it affects general and oral health. This problem increases as vitamin D requirements increase during pregnancy. This study was conducted among pregnant women in urban and rural areas in order to assess the relation between salivary vitamin D3 and dental caries. Materials and methods: In this comparative cross-sectional study, all women participating were attending the primary Health Care Centers in Baghdad city in AL-Karkh sector, they were with age ranged from (15-44) years old. The total number 90 pregnant women in the second trimester only which include: The first group consists of (45) pregnant women attendance seeking dental treatment in urban areas, The second group consists of (45) pregnant women attendance seeking dental treatment in rural areas. Collection of the unstimulated saliva was done according to Tenovuo (1996). After that the clinical examination of Dental caries DMFT/S was performed according to the world health organization in (2013). Results: The findings of this study revealed that the percentage of pregnant women in the age range of 15–29 years was higher in the rural areas than in the urban areas. While those in the age range of 30–44 years were higher in the urban areas. Regarding the age, the percentage of dental caries experience was increased with age. Regarding the area, the percentage of dental caries was higher in the urban area than in the rural area. The highest mean value of DMFT was found in the urban area, with no significant differences. While the highest mean value of DMFS was found in the rural areas with no statistically significant difference, except the FS, where was statistically significant and higher in the urban areas. The mean value of salivary vitamin D3 was found to be higher in rural areas than in urban areas, although statistically non-significant. The correlation between dental caries experience (DMFT/S) and salivary vitamin D3 level was statistically non-significant among urban and rural pregnant women, except in the urban areas where the DMFS was found to be significant with salivary vitamin D3. Conclusions: According to the results of this study, there was a non-significant negative correlation between dental caries and salivary vitamin D3 among pregnant women in urban and rural areas. Except, the correlation between dental caries experience by surfaces and salivary vitamin D3 was negative and significant among urban pregnant women.